(untitled) - Dobyns, Lloyd (New York, 1994)
On balance, this book succeeds in condensing a fair amount of contemporary thinking on quality. The words of the authors, a former journalist and a producer at NBC News, are telling: "Originally, we had intended this book to be more about the Baldrige Award and less about the Deming method, but the more we tried to explain Baldrige, the more we wrote about Deming." Deming, however, is neither the first nor last word on the subject of quality. This work has two flaws. First, it adds little that is substantive to William W. Scherkenback's The Deming Route to Quality and Productivity (1960). Second, it is preceded by Vice President Al Gore's "Creating a Government That Works Better and Costs Less," a government document dated September 7, 1993, which addresses some key issues raised here. Thus, while the book is a good introduction to quality, it is an "also ran" for quality practitioners.
Keywords: Quality control,Total quality management.,Industrial management